The Effect of Leadership Behavior Organizational Culture, Work Motivation, and Decision Making on Work Performance - Aidawati Aidawati; Dewi Widianingsih (FKIP UNIVERSITAS PAKUAN, 2022)
The objective of the research is to determine the direct effects of the State Public Junior High School Principals’ Leadership Behaviour, Organizational Culture, Work Motivation, and Decision Making towards Work Performance. The data were collected through 4 months survey to the State Public Junior High Schools in Bogor Regency and Bogor City involving samples of 62 Principals had been selected from the target population of 102 principals. The path technique was used to analyse the data. The research found positive direct effect of leadership behaviour, organizational culture, work motivation, decision making on work performance; leadership behaviour, organizational culture on work motivation; leadership behaviour, organizational culture, work motivation on decision making. Based on the result of research, this indicates the crucial role of leadership behaviour, organizational culture, work motivation, and decision making on the principals’ work performance. This implies that improved work performance of the State Public Junior High School Principals can be realized through improving on leadership behaviour, organizational culture, work motivation, and decision making. These findings suggest that the leadership behaviour, organizational culture, work motivation, and decision making are important determinants of the principals’ work performance.